The Values of Tauhid Education in the Lyrics of the Song "If Heaven and Hell Never Existed" by Ahmad Dhani - Nurul Wahyu Utami; Ngarifin Shidiq; Nurul Mubin; Robingun Suyud El Syam; Salis Irvan Fuadi; Najmul Laili Fitriana (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2026)
This study aims to examine the values of Tauhid education in the song lyrics “If Heaven and Hell Never Existed” by Ahmad Dhani and their relevance to Islamic Religious Education (PAI) learning. The focus of the study includes the concept of heaven and hell in the Islamic perspective, the history and position of song lyrics within Islamic tradition, the representation of the elements of Tauhid in the song lyrics, and the forms of internalization of Tauhid values in PAI learning. This research employs a qualitative approach with a library-based research design. The primary data consist of the song lyrics, which are analyzed using Roland Barthes’ semiotic approach through three levels of meaning: denotation, connotation, and myth. Secondary data are obtained from the Qur’an, Hadith, Islamic education books, and relevant scholarly literature. Data analysis techniques involve content analysis and semiotic interpretation, which are then linked to the concept of Tauhid education in Islam. The findings indicate that the lyrics of “If Heaven and Hell Never Existed” deeply represent Tauhid values. At the denotative level, the lyrics pose reflective questions regarding human motivation in worship. At the connotative level, the song emphasizes values of sincerity (ikhlas), mahabbah (divine love), and devotion to Allah. At the myth level, the song criticizes transactional forms of worship and affirms the importance of worship that is purely directed to Allah alone. The Tauhid values identified include Tauhid Rububiyah, Uluhiyah, and Asma’ wa Sifat. This study concludes that religious song lyrics can serve as an alternative learning medium in PAI to strengthen the internalization of Tauhid values, particularly in the affective and spiritual domains of students. The use of songs as learning media helps students understand worship in a more contextual, reflective, and meaningful manner.